The house of prisoners : slavery and state in Uruk during the revolt against Samsu-iluna - Seri, Andrea (Studies in Near Eastern records, 2013)
This book studies the house of prisoners at the city of Uruk during the revolt against king Samsu-iluna (ca. 1741-1739 BC). The history of this period is not widely known and there is no previous comprehensive treatment of the institution under consideration. The analysis of some 410 documents dated or attributable to Rim-Anum of Uruk, one of the rebel kings, reveals details about diplomatic dealings between the central power and independent rulers and about the functioning of the house of prisoners of war. This monograph explores state management of captive and enslaved labor in times of poli.